Molecular dissection and an in-silico approach of a novel gibberellin 20-oxidase gene of Hibiscus cannabinus l. - Ab Shukor, Nor Aini; Yu Lok, Yusuf Chong; Kumar, Sures M; Abiri, Rambod; Abdullah, Mohd Puad (Pakistan Botanical Society, 2022)
Kenaf (Hibiscus cannabinus L) is widely grown for its fibre. The Gibberellin 20-oxidase (HcGA20ox) gene is responsible for the improvement in quality of kenaf fibre. The two transcripts designated as HcGA20ox1 (KY399834) and HcGA20ox1 (KY399835) were isolated from the shoot tissue of three-week-old seedlings using the Rapid Amplification of cDNA Ends PCR (RACE), and PCR walking approaches, which encoded the polypeptides of 430 and 345 amino acids, respectively. Therefore, HcGA20ox1b was presumed as a pseudogene and only HcGA20ox1 was focused in downstream works. A high level of similarity has been observed between amino acid sequence of HcGA20ox1 and the GA20ox of other species. In addition, substrate binding site “LPWKET” and two histidine residues which serve as Fe2+ binding domains were found in the sequence. The BLAST results showed that HcGA20ox1 shared high identity with the GA20ox from other species including Gossypium hirsutum, Citrus sinensis, Populus trichocarpa, Jatropha curcas, etc. The highest identity was attributed to the GA20ox of Gossypium hirsutum (accession no.: XP016668427) at 83 identity. Using the Conserved Domain Database (CDD) available in NCBI, the non-heme dioxygenase superfamily, 2OG-Fe (II) oxygenase superfamily and gibberellin 20-oxidase domains were detected in HcGA20ox1. The molecular weight of the protein was 122224.45 with 4.97 theoretical pI.